Ghana - Joint Review of Public Expenditure and Financial Management - World Bank (World Bank, 2012)
This Chapter discusses Ghana's efforts in 2009 and 2010 to restore macro-economic stability through fiscal consolidation. It underlines that a substantial fiscal adjustment was undertaken, and yielded important results in terms of foreign currency reserves position, consumer prices and exchange rate stability. The adjustment mostly took the form of expenditure containment, and had initially a significant impact on overall economic activity through its negative impact on aggregate demand. This effect was compounded by the absence of relay from the private sector, which found it difficult to access credit from a domestic financial sector crippled with non performing loans, the latter originating for a large extent from the continued accumulation of public expenditure arrears. Meanwhile, Ghana improved domestic resource mobilization, though from a low base. This joint review of public expenditure and financial management is an attempt to fill this gap and re-focus attention on public expenditure effectiveness. The review aims at providing a comprehensive picture of public expenditure patterns. It focuses on a set of sectors, such as health and education, as well as on two important cross-cutting issues from a policy perspective, the wage bill and the fiscal decentralization.